Voltage square-wave-injection-based HF parameter identification method for sensorless control of a synchronous reluctance machine - Bugsch, Martha; Piepenbreier, Bernhard; Großmann, Dominik (19th European Conference on Power Electronics and Applications, EPE 2017 ECCE Europe, 2017)
For sensorless control at zero or low speed, extending the bandwidth by higher HF signal-injection frequencies is desirable. Therefore, knowledge of the HF machine parameters for the electrical angle calculation is necessary. Conventional methods to determine the HF machine parameters using sinusoidal signals reach their limits using a standard industrial converter. The restricted switching frequency limits the possible number of voltage steps for sinusoidal-shaped signals of higher frequencies. Moreover, the sampling frequency to reconstruct the current signal also is limited without current oversampling. An alternative and simultaneously simplified signal shape to avoid these limitations is a square-wave-shaped voltage signal. This kind of signal, in contrast to approximately sinusoidal-shaped signals, contains a different amount of higher harmonics if it is realised via pulse-width modulation. Thus, it is not recommended to use HF machine parameters that are measured with sinusoidal-signal injection even if the same frequency would be possible. Hence, a new method needs to be developed to measure the HF machine parameters for this signal shape and HF frequency under the restrictions of a standard industrial converter. This paper proposes a method to estimate the time-discrete transfer function between these square-wave-shaped voltage signal and the resulting current response with a least-square estimation method. A time synchronous averaging algorithm is implemented to reduce the measurement noise of the sampled current values. As a result, the HF admittances necessary for electrical angle estimation can be calculated. Measurement results are also presente
Keywords: "Self-sensing control"; "Eluctance drive"; "Synchronous motor"; "Sensorless control"